IL-15/IL-15Rα in SJS/TEN: Relevant Expression of IL15 and IL15RA in Affected Skin - Teresa Bellón; Olga González-Valle; Elena Sendagorta; Victoria Lerma; Javier Martínez del Río; Celia Martínez; Guillermo Servera; Carlos González-Herrada; Lucía Cachafeiro; José A. Lorente; Rosario Cabañas; Pedro Herranz; et al. (Biomedicines, 2022)
Stevens–Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) is a life-threatening hypersensitivity reaction to medications characterized by keratinocyte apoptosis and skin detachment. IL-15 serum levels have been associated with severity and prognosis of SJS/TEN. We have measured IL-15 concentrations in serum and blister fluid (BF) from patients with SJS/TEN by ELISA and used quantitative RT-PCR to analyze the expression of IL15 and IL15RA (encoding for IL-15 Receptor-α chain) genes in peripheral blood and BF cells, including isolated monocytes, and in affected skin. A positive correlation was found between IL-15 serum levels and a percent of detached skin. BF concentrations were higher, but no correlation was found. Higher IL15 and IL15RA gene expression levels were found in skin-infiltrating blister fluid cells compared to peripheral mononuclear cells. Moreover, IL15RA transcripts were barely detected in healthy skin, being the highest expression levels found in samples from two SJS/TEN patients who did not survive. The cutaneous expression of IL-15Rα in SJS/TEN may provide an explanation to the tissue-specific immune cytotoxic response in this clinical entity, and the results suggest that the effects of IL-15 in SJS/TEN patients may be dependent on the expression of its private receptor IL-15Rα in affected skin.